From more sustainable isocyanide-based multicomponent reactions to spiro-heterocyclic compound syntheses - Salami, Sodeeq Aderotimi (Rhodes University, Faculty of Science, Department of Chemistry)
The global pharmaceutical industry has undergone profound transformations in the past two decades in the search for new drugs. For this reason, most pharmaceutical companies made significant investments not only in the development of new drugs but new methodologies. Modern drug development is confronted with the challenge of developing chemical reactions that are highly capable of providing most of the elements of structural complexity and diversity with the fewest possible synthetic steps for the specific target with the most intriguing properties. The discovery of more sustainable, environmentally friendly reactions capable of forming multiple bonds in a single step has been a challenge in organic synthesis over the years. Many organic chemists have recently started focusing on creative ways of reducing environmental pollution. The use of hazardous solvents has been reduced or eliminated in research to limit harm to both people and the environment. The pursuit of this goal has drawn many organic chemists to the study of various sustainable synthetic techniques including catalysis, aqueous organic reactions and mechanochemistry. The scope of this thesis was to apply sustainable techniques to design multicomponent synthetic protocols for the Passerini reaction and further apply these new protocols to construct spiro-heterocyclic compounds, all based on green chemistry principles. There is a need to develop rapid, efficient, and versatile strategies for the synthesis of bioactive molecules via multicomponent reactions. This project tried to avoid some of the pitfalls of traditional approaches, such as toxicity, low yield, long reaction times, harsh conditions, experimental complexity, and limited functionalization scope. This was achieved by focussing on the use of isonitriles and isothiocyanates as key reactive intermediates, and making extensive use of aqueous reaction conditions, mechanochemistry and microwave activation.
Keywords: Passerini reaction; Isocyanides; Isothiocyanate; Mechanical chemistry; Organic reaction